Quantification of Glucose Metabolism and Nitrogen Utilization in Two Brassicaceae Species under Bicarbonate and Variable Ammonium Soil Conditions - Antong Xia; Yanyou Wu; Jiqian Xiang; Hongqing Yin; Jiajia Ming; Zhanghui Qin (Plants, 2023)
In karst habitats under drought conditions, high bicarbonate (high pH), and an abundant nitrate soil environment, bicarbonate regulates the glycolysis (EMP) and pentose phosphate pathways (PPP), which distribute ATP and NADPH, affecting nitrate (NO3−) and ammonium (NH4+) utilization in plants. However, the relationship between EMP PPP and NO3−, and NH4+ utilization and their responses to bicarbonate and variable ammonium still remains elusive. In this study, we used Brassica napus (Bn, a non-karst-adaptable plant) and Orychophragmus violaceus (Ov, a karst-adaptable plant) as plant materials, employed a bidirectional nitrogen-isotope-tracing method, and performed the quantification of the contribution of EMP and PPP. We found that bicarbonate and ammonium inhibited glucose metabolism and nitrogen utilization in Bn under simulated karst habitats. On the other hand, it resulted in a shift from EMP to PPP to promote ammonium utilization in Ov under high ammonium stress in karst habitats. Compared with Bn, bicarbonate promoted glucose metabolism and nitrogen utilization in Ov at low ammonium levels, leading to an increase in photosynthesis, the PPP, carbon and nitrogen metabolizing enzyme activities, nitrate/ammonium utilization, and total inorganic nitrogen assimilation capacity. Moreover, bicarbonate significantly reduced the growth inhibition of Ov by high ammonium, resulting in an improved PPP, RCRUBP, and ammonium utilization to maintain growth. Quantifying the relationships between EMP, PPP, NO3−, and NH4+ utilization can aid the accurate analysis of carbon and nitrogen use efficiency changes in plant species. Therefore, it provides a new prospect to optimize the nitrate/ammonium utilization in plants and further reveals the differential responses of inorganic carbon and nitrogen (C-N) metabolism to bicarbonate and variable ammonium in karst habitats.